ANALISIS ERROR UNTUK PERSAMAAN RADIOSITAS PADA KURVA TANPA PENGHALANG - Vianney Any Herawati, Maria
Abstract : The radiosity equation occurs in computer graphics. We consider the behaviour of the radiosity integral operator, for smooth and piece-wise smooth curves. For solving the radiosity equation, we used and analyzed the collocation method. The method uses piecewise linear interpolation; and it is also shown that superconvergence results are obtained when solving on a smooth surface.